Sistem Informasi Pengelolaan Perjalanan Dinas Berbasis Mobile Web di Dinas Penanaman Modal ESDM dan Transmigrasi Provinsi Gorontalo - Fadhilah Linti Olilingo; Roviana H. Dai; Rahman Takdir (Gorontalo State University, 2021)
Official travel is a trip carried out by employees in an institution/company related to official duties. Official travel occurs in each institution, for instance, at the Office of Investment, Energy and Mineral Resources, and Transmigration in Gorontalo Province. Yet, there are several problems encountered in the official travel system. The problem is that institution's data recap regarding official travel will be lost every year. Another problem is in the process of report filling, where the report filling can only be performed by the treasurer. As a result, the treasurer has difficulties since s/he must input various reports, and it took a long time. Equally important,as long as the report has not been filled in, the employees cannot perform official travel. Based on the problem above, the proposed solution is creating an information system that can facilitate the treasurer in managing the data of employees and searching the annual reports. Keywords: Offiaical Travel, Official Travel System